2015
DOI: 10.5937/savteh1502005b
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of oregano (Origanum vulgare L.): And basil (Ocimum basilicum L.): Extracts

Abstract: The commercial samples of aerial parts of Origanum vulgare L. and Ocimum basilicum L. (Lamiaceae) were tested for antimicrobial activity. The activity of the extracts with different polarity was tested against a panel of microorganisms, including laboratory strain Helicobacter pylori NCTC 12868. The tested extracts showed a moderate activity. The extracts of O. vulgare were more active against bacteria, especially against Gram positive bacteria with the minimal inhibitory concentration (MIC) between 62.5 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 37 publications
0
17
1
2
Order By: Relevance
“…Several studies have demonstrated that oregano extracts inhibit the growth of certain types of bacteria [ 14 , 17 , 19 ]. In this study, although we have documented that EOE appears to exert its anti-inflammatory properties by lowering cytokine production, we were concerned that the decrease in pro-inflammatory mediator production was not due to the anti-inflammatory properties of EOE, but instead to the anti-bacterial effect of EOE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that oregano extracts inhibit the growth of certain types of bacteria [ 14 , 17 , 19 ]. In this study, although we have documented that EOE appears to exert its anti-inflammatory properties by lowering cytokine production, we were concerned that the decrease in pro-inflammatory mediator production was not due to the anti-inflammatory properties of EOE, but instead to the anti-bacterial effect of EOE.…”
Section: Resultsmentioning
confidence: 99%
“…For many years, this flavoring herb has been widely used as spices in daily life, as well as traditional medicines worldwide to treat numerous conditions and symptoms, including relieving rheumatic, digestive or respiratory disorders, lowering blood cholesterol and glucose levels, and also for calming menstrual problems and suppressing the progress of certain tumors [ 8 , 9 ]. Recent in vitro and in vivo studies have demonstrated that extracts of O. vulgare have anti-oxidative [ 10 ], hepatoprotective [ 11 ], anti-diabetic, anti-inflammatory, anti-apoptotic [ 12 , 13 ], and anti-microbial properties [ 14 ]. Like other aromatic herbs, oregano leaf is also a rich source of numerous phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…vulgare [ 1 , 3 ]. In terms of chemical composition, research on O. vulgare species from various countries have previously been reported: Italy [ 4 ], Greek [ 5 , 6 ], Serbia [ 7 ], Egypt [ 8 ], Pakistan [ 9 , 10 ], China [ 10 ], India [ 11 ], Iraq [ 12 ], Macedonia [ 13 ]. Representatives of the following important classes of active principles were revealed: essential oil (with carvacrol and/or thymol, linalool, and p -cymene), polyphenols (flavonoids and phenolic acids), triperpenoids, and sterols [ 8 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of antibiotic-resistant H. pylori strains and the side effects associated with the present chemotherapeutic approach driven the search for alternatives to currently available anti-H. pylori drugs, especially regarding safe and effective non-antibiotic agents 9 . Thus, the search for novel H. pylori urease inhibitors in natural products such as plant extracts 10 , honey 11,12 and propolis, with improved stability and low toxicity, is mandatory to improve the quality of life of human with H. pylori infection.…”
Section: Introductionmentioning
confidence: 99%